2014
DOI: 10.1039/c4cc03394a
|View full text |Cite
|
Sign up to set email alerts
|

A photoresponsive glycosidase mimic

Abstract: Azobenzene-3,3'-dicarboxylic acid exists in photoisomerizable (E) and (Z)-forms. Deprotonation of the carboxylic acid groups from the (E)-form occurs simultaneously, whereas in the (Z)-form it occurs in a stepwise fashion. The mono anionic form of the (Z)-isomer acts as a glycosidase mimic that proceeds through a general acid-general base catalytic mechanism. This is the first example of a photoresponsive glycosidase mimic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 51 publications
(5 reference statements)
1
46
0
2
Order By: Relevance
“…The peaks at δ 7.83, 7.34 and 7.20 corresponding to the aromatic protons of the azobenzene unit, gradually decreased in the presence of 366 nm UV light, and were accompanied by upfield shifts with the appearance of three new peaks at δ 7.08, 7.02, and 6.60, corresponding to the same set of aromatic protons. This behavior is consistent with the expected behavior for trans to cis conversion of the azobenzene systems …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The peaks at δ 7.83, 7.34 and 7.20 corresponding to the aromatic protons of the azobenzene unit, gradually decreased in the presence of 366 nm UV light, and were accompanied by upfield shifts with the appearance of three new peaks at δ 7.08, 7.02, and 6.60, corresponding to the same set of aromatic protons. This behavior is consistent with the expected behavior for trans to cis conversion of the azobenzene systems …”
Section: Resultssupporting
confidence: 90%
“…The peaks at d 7.83, 7.34 and 7.20 corresponding to the aromatic protons of the azobenzene unit, gradually decreased in the presence of 366 nm UV light, and were accompanied by upfield shifts with the appearance of three new peaks at d 7.08, 7.02, and 6.60, corresponding to the same set of aromatic protons.T his behavior is consistent with the expected behavior for trans to cis conversion of the azobenzene systems. [48,49] It was reported that the eight-memberedd iazocine systems are thermodynamically stable in the cis conformation. [50,51] We have demonstrated thatt he effect of ring strain responsible for the stability of cis form does not extendt ot he 9-membered ring system,a so ur system was found to be more stable in the trans form.…”
Section: Resultsmentioning
confidence: 99%
“…However, catalytic selectivity towards H2O2 production has long been an issue surrounding the direct synthesis approach. With many catalysts often requiring the use of halide [11][12] or acid additives [13] to minimize the over hydrogenation or decomposition pathways, which result in the unselective production of H2O, as shown in Figure 1. Bimetallic AuPd catalysts have been shown to be significantly more selective towards H2O2 generation compared to analogous Pd supported catalysts, likely due to a combination of ensemble and electronic effects.…”
Section: Introductionmentioning
confidence: 99%
“…External control of catalytic systemsb yl ight is ah ighly challenging and still underdeveloped field of moderno rganic chemistry.I nt he quest for responsive catalytic systems, many advantages arise from the use of light as ac lean, non-invasive stimulus,i nw hich judicious choiceo fi rradiation wavelength may allow precise control over catalyst function, activity and selectivity.Anumber of photoresponsive catalysts have been developed over the last decade, exploiting the established switching properties of azobenzenes,d iarylethenesa nd overcrowded alkenes. [1][2][3][4][5] Promising resultsi np hotochemical control of catalyst activity or selectivity have been achieved through different approaches by harnessing cooperative, [6][7][8][9][10][11][12] steric [13][14][15][16][17][18][19][20] and electronic effects [21][22][23][24][25] of the photo-accessible isomers.…”
Section: Introductionmentioning
confidence: 99%